Financial Inclusion, Nutrition and Socio‐Economic Status Among Rural Households in Guruve and Mount Darwin Districts, Zimbabwe - Murendo, Conrad; Murenje, Gamuchirai; Chivenge, Pepukai Prince; Mtetwa, Rumbidzai (John Wiley and Sons Ltd, 2021)
This article assessed the association between financial inclusion and nutrition among 987 rural households in two districts of Zimbabwe. Poisson and negative binomial regressions were used for model estimations. Financial inclusion increased dietary diversity and food consumption by 12 and 14 per cent, respectively. Using concentration indices, our results show pro‐rich advantages in financial inclusion and household nutrition. Promoting inclusive financial services among rural and poorer households is crucial. This can be achieved through establishing microfinance and agency banking in rural areas. Promoting pro‐poor financial inclusion strategies, for example reduction of transaction and banking fees, is important to enhance equity.